Bhutan : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
Recent economic developments: economic activity and prices; fiscal developments; monetary policy and developments; external sector developments. Eighth Five-Year Plan; background; objectives and strategy; key elements; and sectoral policies. Financial sector developments and reforms. Statistical tables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet